Pengelolaan Laboratorium Kimia Kimia di SMAN 1 Kupang Nusa Tenggara Timur (NTT) - Yanti Rosinda Tinenti; Hironimus Tangi; Yustina D. S. Lawung (Jurnal Pengabdian UntukMu NegeRI, 2021)
Abstract This PKM is conducted at SMA Negeri I Kupang, which is located at JLN. Cak Doko, No. 59, Oetete Village, Oebobo District, Kupang City, NTT Province. The output in this PKM is a well-organized chemical laboratory, producing types of laboratory administration, analyzing the increase in teacher knowledge and skills regarding laboratory administration and governance. The result of this PKM activity was an increase in the value of the ability of teachers in laboratory management and administration which had an impact on the conditions of the chemistry laboratory at SMAN 1 Kupang on 5 governance indicators indicated by N-Gain values ​​and criteria consecutively as follows, planning indicator 0, 62 (moderate), organizing indicator 0.33 (moderate), administration indicator 0.78 (high), laboratory instrument arrangement indicator 1 (high), laboratory material structuring indicator 0.93 (high), and safety indicator 0.67 ( moderate). Thus it can be concluded that this PKM activity can improve teachers' knowledge and skills regarding laboratory governance.